Ctrl-alt-denounce. (Economist, 2021)
The article focuses on the move by the U.S. government to recruit its allies to admonish China for state-sponsored hacking in 2021. Topics discussed include the identification of the Chinese Ministry of State Security (MSS) as the perpetrator of an attack on the Exchange electronic mail server of Microsoft in March, call of the North Atlantic Treaty Organization, European Union and Great Britain for China to end the activity, and the increase in the number of Chinese espionage against the U.S.